A large sinonasal schwannoma: a rare entity - Singh, Manwinder; Bhagat, Sanjeev; Sharma, Dinesh Kumar; Monga, Rabia; Chhabra, Nitin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Schwannoma is a rare neoplasm of nose and PNS which develops from Schwann’s cells of neural sheath and most are benign and encapsulated and amenable to surgical excision. The aim of this write-up is to report a rare case of schwannoma of nose and PNS. We report a case of 40 year old female, a housewife, presented in ENT OPD with complaints of nasal obstruction on right side, post nasal drip and headache. On diagnostic nasal endoscopy, there was a polypoidal mass coming from the middle meatus which was pushing the medial turbinate medially. NCCT and MRI of nose and PNS showed soft tissue density mass involving right ethmoidal air cells, maxillary sinus and bilateral sphenoid sinuses and eroding the lateral wall of right maxillary sinus reaching upto infratemporal fossa, superiorly mass was seen eroding the inferior wall of right orbit. The tumour was removed endoscopically piecemeal and sent for histopathology which showed it to be a schwannoma. The conclusion of the finding was schwannoma involving nasal cavity, maxillary sinus and sphenoid sinus eroded the lateral wall of maxillary sinus going into infratemporal fossa and floor of the orbit. Schwannoma should also be kept as a possibility in the differential diagnosis of tumors of nose and PNS.